Variation in lysine, threonine, and tryptophan availability in meat and bone meal as estimated by the slope‐ratio growth assay technique in growing rats. (15th July 2020) - Sato, Hiroyuki; Miura, Makoto; Fujieda, Takeshi; Taciak, Marcin; Kikusato, Motoi; Toyomizu, Masaaki
Abstract: Meat and bone meal (MBM) is an important protein source used in animal feeds. However, as the composition and availability of amino acids (AAs) in MBM fluctuate markedly, it is important to verify the magnitude of these parameters in different MBMs. In this study, the AA compositions of 19 MBMs were analyzed to confirm variations in lysine (Lys), threonine (Thr), and tryptophan (Trp), then which were compared with those of soybean meal (SBM) and fish meal (FM). Instability in Lys, Thr, and Trp availabilities in six MBMs were also considered after estimation using the slope‐ratio growth assay technique in rats. Variations in AA composition were evaluated using the coefficient of variance (CV: Standard deviation/Mean). CVs for Lys, Thr, and Trp content were 9.40, 11.83, and 18.12 in MBM, 2.71, 2.48, and 3.19 in SBM, and 10.09, 10.44, and 13.47 in FM. Furthermore, means and SDs for Lys, Thr, and Trp availabilities in MBM were 53.3 ± 10.4% (CV: 19.5), 65.9 ± 17.6% (CV: 26.6), and 83.2 ± 11.2% (CV: 13.5), respectively. These results provide the first evidence that variations in MBM AA compositions were 3.5 to 5.7 times higher than those in SBM, but similar to FM, and that the large variation in availability substantially existed.